Pathophysiology and Diagnosis of Vertebrobasilar Insufficiency: A Review of the Literature - Lima Neto, Arlindo Cardoso; Bittar, Roseli; Gattas, Gabriel Scarabotolo; Bor-Seng-Shu, Edson; Oliveira, Marcelo de Lima; Monsanto, Rafael da Costa; Bittar, Luis Felipe (International Archives of Otorhinolaryngology, 2017)
Introduction Vertebrobasilar insufficiency is defined as transitory ischemia of the vertebrobasilar circulation. Dizziness, vertigo, headaches, vomit, diplopia, blindness, ataxia, imbalance, and weakness in both sides of the body are the most common symptoms.Objective To review the literature regarding the three available diagnostic testing in patients with dizziness complaints secondary to vertebrobasilar insufficiency (VBI): magnetic resonance angiography; transcranial Doppler ultrasound; and vertebrobasilar deprivation testing.Data Synthesis We selected 28 studies that complied with our selection criteria for appraisal. The most frequent cause of the hemodynamic changes leading to VBI is atherosclerosis. The main clinical symptoms are dizziness, vertigo, headaches, vomit, diplopia, blindness, ataxia, imbalance, and weakness in both sides of the body. Even though arteriography is considered the most important exam to diagnose the disease, the inherent risks of this exam should be taken into consideration. The magnetic resonance angiography has been widely studied and is a good method to identify and localize any occlusions and stenosis in both neck and intracranial great vessels.Conclusion Each patient with a suspected diagnosis of VBI should be individually evaluated and treated, taking in consideration the pros and cons of each diagnostic testing and treatment option.
Keywords: vertigo; ischemia; stroke; vertebrobasilar insufficiency; dizziness; pathophysiology